Measurement and modeling of diffusion time dependence of apparent diffusion coefficient and fractional anisotropy in prostate tissue ex vivo. (30th June 2017) - Bourne, Roger; Liang, Sisi; Panagiotaki, Eleftheria; Bongers, Andre; Sved, Paul; Watson, Geoffrey
Abstract : The purpose of this study was to measure and model the diffusion time dependence of apparent diffusion coefficient (ADC) and fractional anisotropy (FA) derived from conventional prostate diffusion‐weighted imaging methods as used in recommended multiparametric MRI protocols. Diffusion tensor imaging (DTI) was performed at 9.4 T with three radical prostatectomy specimens, with diffusion times in the range 10–120 ms and b ‐values 0–3000 s/mm 2 . ADC and FA were calculated from DTI measurements at b ‐values of 800 and 1600 s/mm 2 . Independently, a two‐component model (restricted isotropic plus Gaussian anisotropic) was used to synthesize DTI data, from which ADC and FA were predicted and compared with the measured values. Measured ADC and FA exhibited a diffusion time dependence, which was closely predicted by the two‐component model. ADC decreased by about 0.10–0.15 μm 2 /ms as diffusion time increased from 10 to 120 ms. FA increased with diffusion time at b ‐values of 800 and 1600 s/mm 2 but was predicted to be independent of diffusion time at b  = 3000 s/mm 2 . Both ADC and FA exhibited diffusion time dependence that could be modeled as two unmixed water pools — one having isotropic restricted dynamics, and the other unrestricted anisotropic dynamics. These results highlight the importance of considering and reporting diffusion times in conventional ADC and FA calculations and protocol recommendations, and inform the development of improved diffusion methods for prostate cancer imaging. Abstract : Both ADC and FA exhibited diffusion‐time dependence, which could be modeled as two unmixed water pools—one having isotropic restricted dynamics, and the other anisotropic unrestricted dynamics. These results highlight the importance of considering and reporting diffusion times in conventional ADC and FA calculations and protocol recommendations, and inform the development of improved diffusion methods for prostate cancer imaging.